Agreement between 2D Visual- and 3D Motion Capture-based Assessment of Foot Strike Pattern - Haruhiko Goto; Toshinao Kamikubo; Ryota Yamamoto; Toshiharu Tsutsui; Suguru Torii (International Journal of Sports Physical Therapy)
# Background